Association of kidney functions with a cascade of care for diabetes and hypertension in two geographically distinct Indian cohorts. (June 2021) - Khandpur, Sukhanshi; Bhardwaj, Mansi; Awasthi, Ashish; Newtonraj, Ariarathinam; Purty, Anil J.; Khanna, Tripti; Abraham, Georgi; Tiwari, Swasti
Highlights: We determined care cascade of T2DM & HTN in the North and South Indian cohorts. The South Indian cohort had a better care cascade for CKD-risk factors, T2DM & HTN. Similar low-eGFR proportion, despite less cases with T2DM & HTN in north cohort. Younger participants with mild-to-moderate low eGFR were prevalent in North cohort. Care cascade of T2DM and HTN were associated with lower CVD risk, BUN and optimal eGFR. Abstract: Aim: Type 2 diabetes (T2DM) and hypertension (HTN) are the main modifiable risk factors of chronic kidney disease (CKD), among the known traditional and non-traditional risk factors. Methods: We determined the prevalence and care-cascade of these modifiable CKD-risk factors and their association with socioeconomic status in adjoining Lucknow and Puducherry cities of India. Results: 439 participants reported no CKD were recruited. Serum analysis revealed an Estimated Glomerular Filtration Rate (eGFR) ≥ 90 ml/min/1.73 m 2 in 60.36% of the population. Of them, 55.85% had HTN and/or T2DM as CKD-risk factors; however, less than half of this population was unaware of their CKD-risk status. Awareness and treatment were significantly higher in Puducherry and were associated with literacy, occupation, and residence place. Although the CKD-risk population was about two times higher in Puducherry than Lucknow, the populations with mild-low eGFR were comparable in the two regions. Moreover, in Lucknow, mild-low eGFR and low awareness were more prevalent among the younger participants (<30 years), relative to Puducherry. Conclusions: Despite a higher prevalence of CKD-risk factors in Puducherry, populations with mild-low eGFR were comparable to Lucknow. More heightened awareness and better care cascade for CKD-risk factors in Puducherry may prevent or delay eGFR reduction.